Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery Electrically Mediated Delivery of Molecules to Cells - Jaroszeski, Mark J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
In Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery, leading experts comprehensively review all aspects of the delivery of therapeutic molecules to cells using electrical impulses-i.e., the extraordinarily promising new areas of electrogene therapy, electrochemotherapy, and transdermal drug delivery. Their survey ranges from outlines of the basic physical principles that govern cell permeabilization by pulsed electric fields, to descriptions of the current state-of-the-art in instrumentation and electrodes, to summaries of preclinical and clinical trial results. The authors focus on drug, gene, and transdermal delivery techniques, providing detailed examples of drug delivery using electric fields from a variety of pulse generators and electrodes. The protocols cover almost every variation in procedure and/or apparatus so that investigators can readily identify the method needed for their own work, or adapt one to their particular purposes. Comprehensive and authoritative, Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery provides entré to an immensely practical set of in vivo electroporation techniques, including electrogene therapy, electrochemotherapy, and transdermal drug delivery-techniques holding great promise for all those working toward better therapies for in cancer, metabolic diseases, and vaccination.
Reviews -- Principles of Membrane Electroporation and Transport of Macromolecules -- Instrumentation and Electrodes for In Vivo Electroporation -- Numerical Modeling for In Vivo Electroporation -- In Vitro Delivery of Drugs and Other Molecules to Cells -- The Basis of Electrochemotherapy -- Electrochemotherapy -- Clinical Trials for Solid Tumors Using Electrochemotherapy -- In Vitro and Ex Vivo Gene Delivery to Cells by Electroporation -- Delivery of Genes In Vivo Using Pulsed Electric Fields -- Mechanism of Transdermal Drug Delivery by Electroporation -- Mechanistic Studies of Skin Electroporation Using Biophysical Methods -- Electrochemotherapy Protocols -- Treatment of Murine Transplanted Subcutaneous Tumors Using Systemic Drug Administration -- Electrochemotherapy of Murine Melanoma Using Intratumor Drug Administration -- Treatment of a Tumor Model with ECT Using 4+4 Electrode Configuration -- Treatment of Multiple Spontaneous Breast Tumors in Mice Using Electrochemotherapy -- Electroporation of Muscle Tissue In Vivo -- Treatment of Human Pancreatic Tumors Xenografted in Nude Mice by Chemotherapy Combined with Pulsed Electric Fields -- Distribution of Bleomycin in a Rat Model -- Treatment of Rat Bladder Cancer With Electrochemotherapy In Vivo -- Electrochemotherapy for the Treatment of Soft Tissue Sarcoma in a Rat Model -- Treatment of Spontaneous Soft Tissue Sarcomas in Cat -- Treatment of Rat Glioma With Electrochemotherapy -- Treatment of Liver Malignancies with Electrochemotherapy in a Rat Model -- Treatment of Liver Tumors in Rabbit -- Electrogenetherapy Protocols -- Electrically Mediated Reporter Gene Transfer into Normal Rat Liver Tissue -- Reporter/Functional Gene Transfer in Rat Brain -- In Vivo Gene Electroporation in the Mouse Testis -- Ex Vivo Stromal Cell Electroporation of Factor IX cDNA for Treatment of Hemophilia B -- In Ovo Gene Electroporation into Early Chicken Embryos -- Transdermal Delivery Protocols -- Electrical Impedance Spectroscopy for Rapid and Noninvasive Analysis of Skin Electroporation -- An In Vitro System for Measuring the Transdermal Voltage and Molecular Flux Across the Skin in Real Time -- Using Surface Electrodes to Monitor the Electric-Pulse-Induced Permeabilization of Porcine Skin -- Transdermal Delivery Using Surface Electrodes in Porcine Skin -- Transdermal Drug Delivery by Skin Electroporation in the Rat -- In Vivo Skin-Targeted Gene Delivery by Pulsed Electric Fields.
Keywords: Cell biology; Cell Biology